The Role Of The Jadids In Elevating The Spirituality Of The People Of Turkestan - Sultonova Shaxnoza Sadriddinovna (Penerbit Jurnal Indonesia, 2024)
This article examines the social, political, and cultural significance of the Jadid movement that took shape in the late 19th and early 20th centuries in Turkestan. It highlights the processes associated with national self-awareness, the restoration of education, enlightenment, and national values, as well as reforms aimed at achieving progress. The article also analyzes the movement’s activities through its three main fields: education, art, and the press, and its efforts to strengthen national consciousness and religious beliefs. It demonstrates how the essence of the movement, its struggle to preserve national identity under colonial conditions, and its alignment with the pressing democratic ideas of the time, were interwoven. The study is aimed at illustrating the historical significance of the movement in shaping national consciousness and adapting society to modern development.